Identifikasi Pasien Sepsis Rumah Sakit Ibnu Sina Makassar - Qarinah, Maryam; Mangarengi, Yusriani; Mulyadi, Farah Ekawati; Wiriansya, Edward Pandu; Abdi, Dian Amelia (Yayasan Citra Cendekia Celebes, 2023)
Sepsis is one of the causes of considerable morbidity, mortality and health expenditure worldwide. Several factors that influence the high mortality rate in sepsis cases are identified from several bibliography usually in elder, pregnant women, infants, hospitalized patients, and immunosuppression. The research purpose to identifying sepsis patients in Ibnu Sina Makassar Hospital based on age, sex, type of infection and initial diagnosis. This research was an observational descriptive study conducted using secondary data through medical records of patients with sepsis in Ibnu Sina Hospital during October 2018-December 2020. There were 40 samples cases sepsis found. Most sepsis cases consist of 12 patients (30%) found in 58-67 years old patients, 8 patients (20%) in 48-57 years old patients, 7 patients (17.5%) in 38-47 years old patients, 6 patients (15%) in 68-77 years old patients, 3 patients (7.5%) in 18-27 years old, 2 patients (5%) in 28-37 years old patients, each 1 patients (2.5%) in 78-87 and 88-97 years old patients. There 21 patients (52.5%) sepsis patients were female. Infection type, 80% those happened by bacterial infection and 20% by virus infection. Most primary diagnosed of the patients were pneumonia.